Pesan Komunikasi Verbal Sinden dan Penari dalam Pertunjukan Bajidoran - Apriliyanti Apriliyanti (Program Studi Hubungan Masyarakat Politeknik LP3I, 2021)
This study aims to determine the purpose of sinden and dancers when delivering non-verbal codes to Bajidor (guests, audience) and to find out the meaning of non-verbal messages conveyed by sinden and dancers to Bajidor in the Bajidoran performance at Dago Tea House Bandung. This type of research is qualitative research with a case study analyst blade. Sources of data used in this study are primary and secondary data sources. The technique of determining the informants used was purposive sampling. Data collection techniques used are observation, investigation, interviews, and documents. The results of this study indicate that the Bajidoran show that occurs at Dago Tea House Bandung shows that there is a non-verbal interaction between sinden and dancers and Bajidor. It can be seen that the sinden and dancers convey non-verbal codes to Bajidor with the aim of getting saweran which is used as additional income. There is something interesting behind the interactions that occur, namely the intimate relationship between the sinden and the dancers and the bajidor.